To Know or Not To Know: Strategic Inattention and Endogenous Market Structure - Roberto Cellini; Luca Lambertini; Gianmarco I.P. Ottaviano (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
We model an industry in which a discrete number of firms choose the output of their differentiated products deciding whether or not to consider the impact of their decisions on aggregate output. We show that two threshold numbers of firms exist such that: below the lower one there is a unique equilibrium in which all firms consider their aggregate impact as in standard oligopoly; above the higher threshold there is a unique equilibrium in which all firms disregard that impact as in standard monopolistic competition; between the two thresholds there are two equilibria, one in which all firms consider their aggregate impact and the other in which they do not. We then show that our model of strategic inattention is isomorphic to a model of strategic delegation with managerial compensation based on relative profit performance.
Keywords: D43; L13; 330